Blood flow restriction training enhances punching force and upper body strength in elite boxers: a randomized trial - Awana, Gaurav; Rizvi, Moattar Raza; Sharma, Ankita; Aldalaykeh, Mohammed; Zaidi, Zoya; Makhija, Simran; Sami, Waqas; Al-Kuwari, Noof Fahad A. (Frontiers in Physiology, 2025)
IntroductionBoxing demands explosive punching force, yet heavy resistance training risks joint stress and fatigue. Blood Flow Restriction Training (BFRT) offers a low-load alternative that stimulates strength and power gains. This randomized controlled trial investigated BFRT’s effects on upper limb strength and punching force in elite amateur boxers, aiming to establish its value as a safe, performance-enhancing strategy.MethodsThirty elite male amateur boxers (≥3 years of competitive experience) were randomized into an experimental group (BFRT) or a control group. Both groups completed identical upper-body resistance exercises thrice weekly for 8 weeks, The control group trained at 50%–60% 1RM (one repetition maximum), while the BFRT group trained at 20%–30% 1 RM with 40%–50% limb occlusion pressure using standardized 7 cm cuffs. Primary outcomes included 1RM, strength (elbow flexion, extension, bench press) and peak punch force (jab, cross, uppercut, hook) measured via a calibrated vertically-mounted force plate.ResultsAfter 8 weeks, the BFRT group demonstrated significantly greater gains in dominant-arm strength, with 1RM elbow flexion increasing by +3.3 kg (p < 0.001, d = 3.20), elbow extension by +2.95 kg (p < 0.001, d = 2.84), bench press by +13.6 kg (p < 0.001, d = 1.81), and squat by +15.6 kg (p < 0.001, d = 2.05) compared with smaller improvements in controls. Peak Punch force improved markedly in the BFRT group: jab +895 N (p = 0.001, d = 1.52), uppercut +1142 N (p < 0.001, d = 3.02), hook +1157 N (p < 0.001, d = 2.55), and cross +1067 N (p < 0.001, d = 3.80). Repeated-measures ANOVA confirmed strong group × time interaction effects (η2 = 0.27–0.87).ConclusionBFRT led to substantial improvements in upper limb strength and peak punching force in elite boxers using a low-load protocol. These findings suggest BFRT is a safe, effective training strategy that may enhance sport-specific power outputs while potentially reducing joint stress, making it a valuable addition to high-performance boxing programs.